<span>3x + y =3
Y = 2x - 7
substitute </span>Y = 2x - 7 into 3x + y =3
3x + y =3
3x +2x - 7 =3
5x = 10
x = 2
Y = 2x - 7 = 2(2) - 7 = -3
answer
(2, -3)
Another name for a relation is a function.
Answer:
When we multiply or divide by a negative to solve an inequality, it's the same as multiplying or dividing by a negative to solve a regular equation! Just remember to multiply or divide both sides by the same quantity, then simplify! Remember, when multiplying or dividing by a negative <u>YOU MUST FLIP THE INEQUALITY SIGN.</u>
Step-by-step explanation:
You are welcome.
And I hope this helps. :)